La volonté balzacienne comme donnée formelle de La Comédie humaine - Yannick Roy (Itinéraires)
Balzac was not an observer as much as a visionary or a seer, who invented his characters not by basing them on external models, but by becoming them to the point of losing his own identity. That may at first seem to question the credibility of his fiction, but what is left of the author in each of his characters is a quality so tenuous that it does not allow us to recognize him. This quality can be said to be his will, understood here not as a subject matter but as an element of the form, resembling the sort of availability in which Jacques Rivière saw the essence of the adventure novel. Balzac’s method thus forces him to relinquish all attempts at embracing the totality of his Human Comedy, which he builds from the inside without ever seeking to control it.